1995
DOI: 10.1098/rspb.1995.0087
|View full text |Cite
|
Sign up to set email alerts
|

MHC-dependent mate preferences in humans

Abstract: One substantial benefit of sexual reproduction could be that it allows animals (including humans) to react rapidly to a continuously changing environmental selection pressure such as coevolving parasites. This counteraction would be most efficient if the females were able to provide their progeny with certain allele combinations for loci which may be crucial in the parasite-host arms race, for example the MHC (major histocompatibility complex). Here we show that the MHC influences both body odours and body odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
290
4
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 798 publications
(306 citation statements)
references
References 24 publications
10
290
4
2
Order By: Relevance
“…The most intriguing result was that responses to partner infidelity were related to estradiol levels and primarily, although not entirely, during the time of rising and high fertility risk, a pattern that is in keeping with studies of female sexual behavior and mate preferences (Bellis and Baker 1990;Chavanne and Gallup 1998;Gangestad and Thornhill 1998;Penton-Voak and Perrett 2000;Penton-Voak et al 1999;Thornhill and Gangestad 1999;Wedekind et al 1995). It appears that during the time of rising and high fertility risk, high estradiol levels are associated with changes in relative degree of hurt/anger to different forms of partner infidelity (i.e., emotional or sexual), and to "a tendency toward greater distress over a partner's sexual infidelity than emotional infidelity.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The most intriguing result was that responses to partner infidelity were related to estradiol levels and primarily, although not entirely, during the time of rising and high fertility risk, a pattern that is in keeping with studies of female sexual behavior and mate preferences (Bellis and Baker 1990;Chavanne and Gallup 1998;Gangestad and Thornhill 1998;Penton-Voak and Perrett 2000;Penton-Voak et al 1999;Thornhill and Gangestad 1999;Wedekind et al 1995). It appears that during the time of rising and high fertility risk, high estradiol levels are associated with changes in relative degree of hurt/anger to different forms of partner infidelity (i.e., emotional or sexual), and to "a tendency toward greater distress over a partner's sexual infidelity than emotional infidelity.…”
Section: Resultssupporting
confidence: 67%
“…Females who are not taking hormone-based birth control exhibit, as a group, systematic changes in cognition, sexual behavior, and mate preferences during the second week of the menstrual cycle, that is, during the time of rising and high fertility risk (Bellis and Baker 1990;Chavanne and Gallup 1998;Gangestad and Thornhill 1998;Kimura 1999;Penton-Voak and Perrett 2000;Penton-Voak et al 1999;Thornhill and Gangestad 1999;Wedekind et al 1995;Wilcox et al 2000). Bellis and Baker found that females who engage in an extra-pair copulation are most likely to do so during the time of high fertility risk and are less likely to use a contraceptive than during copulations with their long-term social partner.…”
Section: Female Sexuality and The Menstrual Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…In fact numerous studies have linked MHC molecules to mate choice through scent in various species including humans. [41][42][43] In mice, non-canonical MHC class I molecules are specifically expressed in a particular section of the vomeronasal organ (VNO), 44 which are thought to modulate the response to MHC antigens. 45 Given that humans do not have a VNO, it is unclear how they could be able to distinguish different HLA types.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been observed in several vertebrate species [2][3][4], but the question of MHC-dependent mate choice in humans, despite attracting considerable attention, has generated intense controversy (see [5] for a review). Studies of odour preferences support the hypothesis that humans are able to differentiate between the MHC composition of potential mates through olfactory cues, but disagree on whether 'smellers' prefer the odour of MHC dissimilar individuals [6][7][8], or of MHC intermediately related individuals [9]. Moreover, there is corroborating evidence suggesting that individuals with higher heterozygosity at MHC loci are found more facially attractive [10][11][12], and the degree of MHC relatedness between potential mates may also influence facial preferences, either positively [13] or negatively [11].…”
Section: Introductionmentioning
confidence: 99%